Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1101/2021.06.22.21259280
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Using deep learning to predict brain age from brain magnetic resonance images and cognitive tests reveals that anatomical and functional brain aging are phenotypically and genetically distinct

Abstract: With the world population aging, the prevalence of age-related brain diseases such as Alzheimer’s, Parkinson’s, Lou Gehrig’s, and cerebrovascular diseases. In the following, we built brain age predictors by leveraging 46,000 brain magnetic resonance images [MRIs] and cognitive tests from UK Biobank participants. We predicted age with a R-Squared [R2] of 76.4±1.0% and a root mean squared error of 3.58±0.05 years and identified the features driving the prediction using attention maps. We defined accelerated brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…Recent studies have shown that bone mineral density, blood pressure, and type 2 diabetes are associated with delta age 7 , 8 . Genome-wide association analyses identified that KANSL1, MAPT-AS1, CRHR1, NSF in chromosome 17, KLF3 (chromosome 4), RUNX2 (chromosome 6), and NKX6-2 gene (chromosome 10) were significantly associated 5 , 10 , 11 . When combined with the cognitive test results, SNPs in MED8, COLEC10, and PLIN4 genes were also significantly associated 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that bone mineral density, blood pressure, and type 2 diabetes are associated with delta age 7 , 8 . Genome-wide association analyses identified that KANSL1, MAPT-AS1, CRHR1, NSF in chromosome 17, KLF3 (chromosome 4), RUNX2 (chromosome 6), and NKX6-2 gene (chromosome 10) were significantly associated 5 , 10 , 11 . When combined with the cognitive test results, SNPs in MED8, COLEC10, and PLIN4 genes were also significantly associated 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Franke et al [3] used principal component analysis and relevance vector machine to predict age reliably. Studies since then primarily used neural network models for data-driven feature extraction going beyond an arbitrary selection of features [4][5][6][7][8][9][10][11]. The convolutional neural network (CNN) models have been used with a satisfactory level of accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that bone mineral density, blood pressure, and type 2 diabetes are associated with delta age [6, 7]. Genome-wide association analyses identified that KANSL1, MAPT-AS1, CRHR1, NSF in chromosome 17, KLF3 (chromosome 4), RUNX2 (chromosome 6), and NKX6-2 gene (chromosome 10) were significantly associated [5, 9, 10]. When combined with the cognitive test results, SNPs in MED8, COLEC10, and PLIN4 genes were also significantly associated [10].…”
Section: Introductionmentioning
confidence: 99%